UTILIZING E-MODULES TO ENHANCE STUDENTS’ ACHIEVEMENT IN UNDERSTANDING SMAW WELDING DEFECT ANALYSIS AT SMK N 5 SEMARANG - Muhamad Reza Wahyu Prasetyo; Muhammad Khumaedi; Kriswanto; Ruben Bayu Kristiawan; Tegar Oki Prasdika (Universitas Negeri Semarang, 2025)
Understanding welding defect analysis is a crucial competency in vocational welding education, especially in ensuring the quality and safety of welding outcomes. However, many students struggle to master this material due to the lack of interactive and adaptive learning media. This study aims to develop and implement an electronic module (e-module) to enhance student learning outcomes in Shielded Metal Arc Welding (SMAW) defect analysis at SMK N 5 Semarang. The research uses a Research and Development (R&D) approach based on the 4D model: Define, Design, Develop, and Disseminate. A one-group pre-test post-test design was used, involving 33 Grade XI Mechanical Engineering 2 students. The e-module was validated by experts and classified as